2016
DOI: 10.1016/j.cca.2015.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Cut-off values to rule out urinary tract infection should be gender-specific

Abstract: The diagnosis of urinary tract infection (UTI) by urine culture is an expensive and time-consuming procedure. Using a screening method, to identify negative samples, would improve the procedure and reduce costs. In this study, urine flow cytometry, of over 7000 urine samples, was assessed by retrospective analysis. With a cut-off value of >200bacteria/μl, we obtained a sensitivity of 93.0%, a specificity of 63.5%, and a negative predictive value (NPV) of 96.2%. As a result the culturing of 49% of all samples c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Therefore, gender-specific bacterial and leucocyte cut-offs are needed to mainly improve the diagnostic performance in men. This view is also supported by other studies concerning the UF-1000i and its precursor, the UF-500 [15][16][17]. In addition, focusing on cut-off values based on the highest possible accuracy also showed that in men a higher overall accuracy existed at lower cut-off values for both UF-1000i leucocyte and bacterial count, reflecting better specificity in men compared to women for both parameters.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, gender-specific bacterial and leucocyte cut-offs are needed to mainly improve the diagnostic performance in men. This view is also supported by other studies concerning the UF-1000i and its precursor, the UF-500 [15][16][17]. In addition, focusing on cut-off values based on the highest possible accuracy also showed that in men a higher overall accuracy existed at lower cut-off values for both UF-1000i leucocyte and bacterial count, reflecting better specificity in men compared to women for both parameters.…”
Section: Discussionsupporting
confidence: 76%
“…adequately analysed in the ED setting. Most gender-related studies are situated in the primary care, patient populations are insufficiently described and comparison between genders is lacking [10][11][12][13][14][15][16][17][18][19]. In addition, in contrast to the ED, the majority of cases in the primary care setting are women [3,20].…”
Section: Introductionmentioning
confidence: 99%
“…These will be chosen depending on the characteristics of the analyzed population, which is usually heterogeneous. Furthermore, published data recommended adjusting the cutoff values according to gender and age of the patients to increase detection reliability [ 15 , 23 , 31 , 51 ].…”
Section: Studiesmentioning
confidence: 99%
“…In men, leucocyte esterase was also highly sensitive that can be used to rule out UTIs. It has been proposed that the cut-off of positive urine cultures in men and women should be different,15 and our study showed the difference in the performance in urinalysis tests in men and women. We believe that the classic cut-off for positive urine culture, that is, 10 5 CFU/mL, is the most robust since in general the results of the tests were applicable in various subpopulations, and when additional demographic information is available, a more precise interpretation of urinalysis tests can be made.…”
Section: Discussionmentioning
confidence: 62%
“…Previous urinalysis studies were performed in one specific population such as paediatric and women5 13 or in the whole population without subanalysis on specific subpopulation 14. A comparison of the performance of the urinalysis tests in various subpopulations is therefore difficult15 because studies need to be compared that used difference instruments 16. Despite the long history of the use of urinalysis in documenting UTIs, and despite the renewed interest in urinalysis, no studies have been published on a head-to-head comparison of urinalysis by automated test strip analyser with urinalysis by automated cell count using flow cytometry.…”
Section: Introductionmentioning
confidence: 99%